ศึกษาความเป็นไปได้ในการตัดสินใจปลูกกระเจี๊ยบเขียวภายใต้ระบบเกษตรอินทรีย์ เพื่อเป็นอาชีพเสริมของเกษตรกรตำบลบ้านพร้าว อำเภอป่าพะยอม จังหวัดพัทลุง: Study the Possibility of Decision Making about Planting Okra under Organic Agriculture System for a Sideline of Agriculturalists in Ban Prao Subdistrict, Pa Phayom District, Phatthalung Province - Benchasri, Sorapong; Boonchan, Chadarat (Asian Health, Science and Technology Reports, 2011)
This research is study of both quantity and quality of physical, economic and social condition and attitude concerning knowledge and understanding of organic agriculture, attitude and making decision for planting okra under organic agriculture system in order to synthesis the possibility of decision for planting okra under organic agriculture system as a sideline. As from the study, it was found that most of agriculturalists have not yet plant an okra, however possibly, they will make a decision to plant the okra crops as a sideline. Because of their physical, economic and social condition and the attitude of agriculturalists as supporters for planting okra under organic agriculture system. In addition to the knowledge and understanding of agriculturalists concerning organic agriculture and making decision for planting okra of agriculturalists were higher than medium level which was used as an indicator of the possibility to make the decision for planting okra under organic agriculture system in the uneven, lowland areas and deteriorated land. Therefore, okra might be a hopefully alternative plant generating income for agriculturists.